Effect of different immunosuppressive agents on acute pancreatitisS: a comparative study in an improved animal model - Foitzik, Thomas; Forgács, Bence; Ryschich, Eduard; Hotz, Hubert; Gebhard, Martha-Maria; Buhr, Heinz J.; Klar, Ernst (Transplantation, 1998)
Background.Immunosuppressive drugs have been associated with the development and progression of acute pancreatitis after organ transplantation. Consequently, a reduction or a change in immunosuppressive therapy has been recommended once posttransplantation pancreatitis has been suspected. However, it is not known which of the available immunosuppressive agents is most harmful to the pancreas and which may be used safely in this situation. The objective of this study was to investigate the effect of different immunosuppressive drugs in various dosages on intrapancreatic protease activation, acinar cell necrosis, and mortality in an improved model of acute necrotizing pancreatitis in the rat. The rat model of acute necrotizing pancreatitis, like posttransplantation pancreatitis, is characterized by ischemia and microcirculatory disorders. Method. Acute pancreatitis was induced in rats by using a combination of low-dose controlled intraductal glycodeoxycholic acid superimposed on intravenous cerulein hyperstimulation. Six hours thereafter, animals were randomized to intravenous therapy with 2, 10, or 50 mg/kg/day prednisolone(PRED); 3, 15, or 60 mg/kg/day cyclosporine A (CsA); 10 mg/kg/day azathioprine(AZA); 0.6 mg/kg/day orthoclone OKT3 (OKT3); or saline. After 36 hr, surviving animals were killed to determine acinar cell necrosis and trypsinogen activation peptides levels (TAP) in blood and ascites.Results. Compared with saline-treated control rats, animals treated with 60 mg/kg/day CsA developed significantly more acinar cell necrosis and had increased amounts of TAP in ascites. Likewise, there was more extensive acinar cell necrosis in animals subjected to AZA therapy. However, this was not associated with incremental TAP. Animals treated with 3 or 15 mg/kg/day CsA, OKT3, or PRED showed no significant changes in these target parameters. Animals given 10 or 50 mg/kg/day PRED even had decreased hematocrit values and produced significantly less ascites than animals in the other groups.Conclusion.The present results suggest that AZA and high doses of CsA aggravate acute pancreatitis and should, therefore, be avoided once posttransplantation pancreatitis has been suspected, whereas lower doses of CsA, OKT3, and PRED may be used safely. PRED can even be used at higher doses as may be required when graft rejection is suspected.